Adjuvant local antibiotic prophylaxis in Gustilo–Anderson IIIb open fractures: up to 10 years follow-up on clinical outcomes and complications - Eito Asano; Hossai Hemat; Abdullah Bin Sahl; Anand Pillai (Journal of Orthopaedic Surgery and Research)
Abstract Background High-grade open fractures carry a significant risk of osteomyelitis, despite advancements in surgical techniques and treatment protocols. The use of prophylactic, adjuvant local antibiotics is controversially discussed in the literature. CERAMENT®G (BONESUPPORT™) is a novel synthetic bone substitute that effectively elutes gentamicin. This report presents the largest and longest follow-up data collected over the past decade, comparing these findings to our previous findings to identify long-term complications, as well as comparing the outcome against other forms of local antibiotic prophylaxis. Methods A retrospective, descriptive analysis was conducted on patients with Gustilo–Anderson IIIb fractures treated with CERAMENT®G as an adjunct to the conventional fix-and-flap approach from June 2013 to August 2021. Patient demographics, orthoplastic interventions, microbiological findings, and the latest outcome data—including union rates, infection rates, mortality, and amputation outcomes—were extracted from electronic records up to April 2024. Results Seventy-six patients with 78 fractures were included, with a mean follow-up period of 88.7 months. The primary union was achieved in 65 cases (83.3%), and secondary union following bone grafting was achieved in 5 of 13 non-union cases. Three mortalities were identified. Four cases required amputation due to osteomyelitis, flap failure leading to soft tissue infection, failure in bone reconstruction, and chronic pain. Superficial infections occurred in 33 cases (42.3%), and osteomyelitis in 4 cases (5.1%). No local or systemic adverse reactions, including ototoxicity, were reported. Conclusion CERAMENT®G is a safe and effective option for local antibiotic delivery in high-grade open fractures as an adjunct to systemic antibiotic prophylaxis. Its adjunctive use significantly reduced the risk of osteomyelitis compared to systemic prophylaxis alone and was superior to PMMA beads alone.